2016
DOI: 10.3390/su8101058
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Investigation of Resource-Based Cities in Northeastern China

Abstract: Improving the sustainability of traditional resource-based cities in China has been a core issue and policy-priority for Chinese government to establish long-term ecological civilization, particularly for northeastern China which is recognized as a typical agglomeration area of resources cities. In this study, we establish a three-layer index system consisting of a comprehensive layer, systemic layer, and variable layer, and including 22 indicators which are grouped into economic, social and environmental subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 39 publications
(31 reference statements)
0
43
0
3
Order By: Relevance
“…Finally, using a multiple criteria decision method they measured and ranked the sustainability of these cities and with a geographical information system they mapped the sustainability in terms of the spatial effects among these cities [31]. In the same geographical area but with 15 different Sub-Provincial Cities in China, proposed a novel urban green economy evaluation model [32].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, using a multiple criteria decision method they measured and ranked the sustainability of these cities and with a geographical information system they mapped the sustainability in terms of the spatial effects among these cities [31]. In the same geographical area but with 15 different Sub-Provincial Cities in China, proposed a novel urban green economy evaluation model [32].…”
Section: Methodsmentioning
confidence: 99%
“…For city sustainability evaluation, the selection of sustainable indicators is a key factor influencing the conclusions of the evaluation. The three-pole or three-pillar model that combines social system, economic system, and environment system together are widely used because of its concise and comprehensive features [19][20][21][22][23]. Ding et al indicate that the sustainable development of the city is a harmonious and comprehensive development of the three elements [24].…”
Section: Related Work On City Sustainability Evaluationmentioning
confidence: 99%
“…Yi et al develop the deviation maximization weighting method to observe the sustainable levels of 17 cities in Shandong Province, China [11]. Several studies on city sustainability evaluation can be found, and the related literature can be grouped into three categories, i.e., evaluation indicators selection [19][20][21][22][23][24][25][26][27][28], indicators' weights setting [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and information aggregation [44][45][46][47][48][49][50][51][52]. A detailed review of the related work is shown in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al selected entropy as the basic method used to analyze the sustainability of urban ecosystems in Guangzhou, China [25]. Lu et al used the coefficient-variation method to determine criteria weights in the process of investigating the sustainability of resource-based cities in Northeastern China [26]. Van de Kerk et al constructed a sustainable society index with equal weights to measure sustainable development in the country region [27].…”
Section: Introductionmentioning
confidence: 99%